Valorization of Selected Biomass-Derived Molecules on Olea europaea Leaves-Biotemplated TiO2-g-C3N4 Photocatalysts - M. Carmen Herrera-Beurnio; Francisco J. López-Tenllado; Alejandro Ariza-Pérez; Jesús Hidalgo-Carrillo; Rafael Estevez; Juan Martín-Gómez; Francisco J. Urbano; Alberto Marinas (Biomimetics)
Biotemplating technique allows the synthesis of catalysts, recreating the sophisticated structure of nature templates. In this work, some biotemplated TiO2 semiconductors were synthesized using Olea europaea leaves as templates. Then, g-C3N4 was coupled to materials to later incorporate Pt on the surface or as dopant in the structure to evaluate the efficiency of the solids in two photocatalytic applications to valorize biomass: hydrogen production through glycerol photoreforming, and photoacetalization of cinnamaldehyde with 1,2-propanediol. In glycerol photoreforming, the presence of Pt (superficial or dopant) enhanced hydrogen production, being Pt@AOLCN (a heterojunction containing biotemplated TiO2, g-C3N4, and Pt) the system that exhibited the highest efficiency (3053.4 µmol·gcat−1·h−1). For photoacetalization, while Pt reduced cinnamaldehyde conversion, it improved selectivity when incorporated on TiO2. Notably, carbon nitride (CN) exhibited the highest yield after 16 h of testing. The study emphasizes the importance of tailoring catalyst selection to specific reactions, as efficiency is closely tied to the structural and chemical properties of the materials. These findings contribute to the development of efficient photocatalysts for sustainable biomass valorization processes.